Emphasis on Social Functions in Cilacap City Park Planning - Lestariningsih, Dwi Jati (ReTII, 2023)
Population development in Cilacap City is increasing in line with the development of Cilacap City as an industrial city in Central Java. Developments in the industrial and business sectors in the city of Cilacap have had a positive impact in increasing PAD, employment and improving the community’s economy. The negative impacts of the industrial sector include air pollution, reduced interaction between citizens due to busy work. Lack of community interaction will make people tend to be individualistic, making it easy for disputes to occur. Public spaces (city parks) can be a solution to overcome air pollution, as a forum for community activities, and also to fulfill the green open space of Cilacap city to reach 30%. City park planning in Cilacap City emphasizes a social function approach. The city park site plan design was inspired by the shape of the wijayakusuma flower as the symbol of Cilacap City. equipped with sports recreation facilities, and open spaces for interaction between citizens of all ages